Peranan Perhitungan Harga Pokok Produksi Pendekatan Full Costing Dalam Menentukan Harga Jual Dengan Metode Cost Plus Pricing - Noviasari, Evi; Alamsyah, Richad (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The purpose of this study were to know the role of calculation cost of goods manufactured and determination of the selling price of shoes in the Heriyanto’s shoes MSME. To knowing the extent of differences in determination the cost of goods manufactured by using the company method and the full costing approach and compare the selling price according to the company's method with using the Cost Plus Pricing. The type of research used is qualitative research. The analytical method used in this study is qualitative descriptive analysis. The data used in this study are primary data. Data were obtained directly through observation and interviews with the Heriyanto’s shoes MSME and data in the form of information on production costs such as raw material costs, labor costs, and factory overhead costs MSME during December 2018. While for secondary data. Data were obtained from intermediary media such as books or literature, journals related to the title of the research, and can also be via the internet. The results of the study it can be concluded that the cost of goods manufactured calculation according Heriyanto’s MSME is lower than the cost of goods manufactured calculation using the full costing method. The cost of goods manufactured according heriyanto’s MSME is Rp. 15.675/pair or Rp. 313.492/score (Hamer Material) and Rp. 14.600/pair or Rp. 291.992/score (Kavaro Material). While the cost of goods manufactured used the full costing method, which is Rp. 16.310/pair or Rp. 326.201/score (Hamer Material) and Rp. 15.235/pair or Rp. 304.701/score (Kavaro Material). This is caused factory overhead costs that are not calculate by Heriyanto’s MSME such as electricity costs, gas costs, maintenance costs for machinery and factory vehicles, and depreciation costs. Determination of selling price must be appropriately because the determination of selling prices that are too high will result in difficulty competition with similar products while the determination of selling prices too low will result in reduced income generated by Heriyanto’s MSME. The difference in determination the cost of good manufactured will affect the Heriyanto’s MSME in determining the selling price, because the cost of goods manufactured is the main element in determination selling price. Calculation of selling prices according Heriyanto’s MSME is Rp. 18.026/pair or Rp. 360.516/score (Hamer Material) and Rp. 16.790/pair or Rp. 335.791/score (Kavaro material). While the selling price used the Cost Plus Pricing method which is Rp. 18.814/pair or Rp. 376.281/score (Hamer Material) and Rp. 17.578/pair or Rp. 351.556/score (Kavaro material). Keywords : Cost of Goods manufactured, Selling Price, Full Costing, Cost Plus Pricing